Penerapan Model Pembelajaran Preview, Question, Read, Reflect, Recite And Review (PQ4R) Terhadap Keterampilan Membaca Pemahaman Siswa Kelas IV - Ritha Tuken; Nur Ilmi; Andi Randi Rahmat (Universitas Negeri Makassar, 2022)
The problem in this research is the low learning outcomes of fourth grade students. The problem in this study is how the Preview, Question, Read, Reflect, Recite And Review (PQ4R) learning model improves the learning process for reading comprehension skills in fourth grade students of UPT SD Negeri 22 Pinrang and whether the application of the Preview, Question, Read, Reflect, Recite And Review (PQ4R) can improve the learning outcomes of fourth grade students of UPT SD Negeri 22 Pinrang. This study aims to examine the process and learning outcomes using the Preview, Question, Read, Reflect, Recite And Review (PQ4R) learning model. The approach used is an approach approach and the type of research is Classroom Action Research (CAR). The implementation of this research action was carried out in 2 cycles, starting with pre-action activities then in each cycle consisting of 4 stages which included planning, implementation, observation, and reflection. This research instrument uses observation sheets and final evaluation tests in each cycle. The subjects in this study were teachers and fourth grade students of UPT SD Negeri 22 Pinrang in the 2021/2022 academic year which collected 15 students consisting of 9 boys and 6 students. woman. Data analysis techniques are data condensation, data presentation, and conclusion drawing. In the first cycle the research results on the learning process were in sufficient qualification (C) and the learning test results in sufficient qualification (C) while in the second cycle the research results on the learning process were in good qualification (B) and the test learning results were in good qualification (B). The conclusion of this study is that the application of the Preview, Question, Read, Reflect, Recite And Review (PQ4R) learning model can improve the process and student learning outcomes in reading comprehension skills in grade IV UPT SD Negeri 22 Pinrang.